Synthesis, Molecular Docking and SAR Study of Isoniazid Incorporated 2-Sulfanylquinazolines as Novel Inhibitors of Protein Kinase B - A. N. Deshpande, S. C. Dhawale, S. B. Bari, C. G. Bonde (International Journal of Advanced Science and Technology, 2019)
The protein kinase B (PknB) of Mycobacterium tuberculosis is an attractive potential target in sustaining mycobacterial growth. In this study, a new series of isoniazid incorporated 2-sulfanylquinazoline derivatives were synthesized and characterized. These compounds were screened for their in vitro antitubercular activity against Mycobacterium tuberculosis H37Rv strain. The antitubercular results have pointed towards the equal potency of compounds 5B8, 5B9 and 5B10 with minimum inhibitory concentrations (MICs, 6.25 μg/ml) comparable to reference standard streptomycin with  selectivity indices of 1.6, 4.8 and 4 respectively. In vitro cytotoxicity data using THP-1 cells specified that the most potent compounds 5B8, 5B9 and 5B10 were found to be non-toxic (≈50% inhibition). The structure-activity relationships indicated that the electron donating substituents like -NH2, -OH, alkyl groups with aliphatic chain length up to C-4 and aryl groups at position-2 of quinazoline, were identified as key determinants of the antitubercular activity. Docking studies on protein kinase B explained the higher potency of compounds based on binding poses of molecules.